Ethnic People’s Perception on Contribution of Development Sector for Awareness Promotion: Evidence from Lalitpur, Nepal - Byanjankar, Sama; Devkota, Niranjan; Mahapatra, Sushanta; Prajuli, Seeprata (Quest Journal of Management and Social Sciences, 2024)
Background: Research has been conducted on the relationship between development sectors and ethnic groups. Developmental sectors work to eliminate poverty, provide education, health care, basic support, and risk prevention, among other things, but evidence shows that their awareness-raising efforts are insufficient. Objective: The objective of the study was analyzing contribution of developmental sectors for awareness promotion in Lalitpur district. Methods: The Binary Logit Model was chosen as the primary study of research in order to find reality. To examine the data quantitative, descriptive and inferential statistics was used. A convenience sampling with a sample size of 281 respondents was chosen for the study based on practical experience and adequate knowledge about development sectors contribution regarding awareness promotion. Results: The study shows that development sectors support an awareness programs, its engagement has significant relationship with ethnic people development and increase level of knowledge and awareness level. Ethnic groups are still expecting quality service and other campaign from developmental sectors. Majority of the respondents argued that proper advertising and sharing information related programs can lead to better service for ethnic people and solve major problems such as management issues, knowledge, information etc. Conclusions: The research concludes that the more development activities and people’s participation in the awareness programs, better the performance leading with enhancement of the ethnic people prosperity and happiness as well as the ethnic society and economic development vice versa. Developmental sectors should focus on removing problems engaging together with ethnic people and developmental sectors. Development sector should promote its advertisement campaign in better way along with gathering more information to benefit and provide better service to ethnic people of Lalitpur district. JEL Classification: L31, O19, O38, C83, I38